2017
DOI: 10.1590/0103-6440201600994
|View full text |Cite
|
Sign up to set email alerts
|

AgNPs: The New Allies Against S. Mutans Biofilm - A Pilot Clinical Trial and Microbiological Assay

Abstract: The purpose of this study was to evaluate the antimicrobial properties of a new formulation containing silver nanoparticles, named Nano Silver Fluoride (NSF), to inhibit Streptococcus mutans biofilm formation on children's dental enamel. The variations in dental biofilm pH and in the Simplified-Oral-Hygiene-Index (OHI-S) also were evaluated after the treatment with NSF. This was a randomized, double-blind, crossover and prospective pilot clinical trial study in which 12 schoolchildren, aged between 7-8 years, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 22 publications
0
16
0
1
Order By: Relevance
“…In this study, the S. mutans counts and Lactobacillus counts were evaluated in saliva. S. mutans were cultured using MSB agar[ 5 ] and Lactobacilli in Rogosa agar,[ 6 ] which are the selective media for the growth of S. mutans and Lactobacilli , respectively. Studies reveal that the results obtained by this culture plate method, as used in this study, correlate well with the dip slide methods,[ 7 8 ] yet another method used for the same.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the S. mutans counts and Lactobacillus counts were evaluated in saliva. S. mutans were cultured using MSB agar[ 5 ] and Lactobacilli in Rogosa agar,[ 6 ] which are the selective media for the growth of S. mutans and Lactobacilli , respectively. Studies reveal that the results obtained by this culture plate method, as used in this study, correlate well with the dip slide methods,[ 7 8 ] yet another method used for the same.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the present study are consistent with previous studies. [22][23][24][25][26][27] Jain et al, 22 noticed that there was a significant decrease in plaque score in CHX group at 15 days and 30 days. In this study, a significant reduction in PLI, GI and BPI at two and four weeks was found after using CHX mouthwash.…”
Section: Discussionmentioning
confidence: 99%
“…et al,24 who reported NS antibacterial activity against Porphyromonas gingivalis Shawky et al,25 showed that NS resulted in a pronounced improvement in clinical parameters and reduction of microbial infections. Lu et al,26 showed that NS had apparent antibacterial effects against five anaerobic oral pathogenic bacteria and aerobic bacteria.Freire et al,27 also showed that NS significantly reduced the CFUs four fold in 24 hours. Sadeghi et al,28 reported that NS had bactericidal effects against Streptococcus mutans comparable to CHX.…”
mentioning
confidence: 91%
“…In addition to active and effective antibacterial treatment, NPs also play a major role in the field of prevent the oral diseases. Nanoparticles of sodium fluoride (NSF) fluoride-based varnishes showed expected antibacterial effects when compared to silver diamine fluoride (SDF) varnishes—the gold standard for anticariogenic agents [165,166,167]. The toothbrush impregnated with AgNPs reduced the number of the putative periodontal pathogens [168,169].…”
Section: Antimicrobial Applications In Dentistrymentioning
confidence: 99%